ANALISIS KETIMPANGAN PEMBANGUNAN DI INDONESIA TAHUN 2010-2020 - Masrida Zasriati (Al Dzahab: Journal of Economics, Management, Business and Accounting, 2022)
This study aims to determine how big the level of inequality in Indonesia is and to find out how Klassen's typology in Indonesia is. The data used is secondary data obtained from the official website of the Central Statistics Agency (BPS), then analyzed using the Theil Index and Typology Klassen formulas, with the following research results: 1. Development inequality by province in Indonesia is low or evenly distributed with the Theil index value ranging from 0.01-0.05 or with an average of 0.03 approaching 0. 2. Typology of Klassen Indonesia, which is included in the fast-growing and fast-growing regions (Quadrant I), namely DKI Jakarta Province, and the Archipelago Riau, for the provinces of Riau, East Kalimantan, North Kalimantan, West Papua, and Papua, are included in the developed but depressed regions (Quadrant II), while the provinces of North Sumatra, West Sumatra, Jambi, Bengkulu, West Java, East Java, Banten, Bali , Central Kalimantan, North Sulawesi, Central Sulawesi, South Sulawesi, Southeast Sulawesi, Gorontalo, West Sulawesi, Maluku, and North Maluku, are included in the fast developing areas (Quadrant III), and the Provinces of Aceh, South Sumatra, Lampung, Kep. Bangka, Central Java, DI Yogyakarta, East Nusa Tenggara, West Nusa Tenggara, West Kalimantan, and South Kalimantan, are included in the relatively underdeveloped areas (Quadrant IV).